2019
DOI: 10.5812/jamm.95457
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Kidney, Renal Pelvis, and Ureter Cancers in Isfahan Province, Iran

Abstract: Background: According to the literature, the incidence of kidney cancer is on the rise worldwide. Objectives: The aim of this investigation was to provide the data of period prevalence of kidney, renal pelvis, and ureter cancers in the general population including the military or non-military population in Isfahan province, Iran. Methods: Data associated with cancers of the kidney, renal pelvis, and ureter were obtained from the Isfahan Cancer Registry between 2011 and 2015. Kidney, renal pelvis, and ureter ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…The results of this study indicated that the incidence rate of kidney and ureter cancers had an increasing trend over 13 years, which is similar to the results of other studies conducted in Iran (15,18). Xu et al showed that over the past 30 years, the ASIR of kidney cancer has tripled in China (22).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results of this study indicated that the incidence rate of kidney and ureter cancers had an increasing trend over 13 years, which is similar to the results of other studies conducted in Iran (15,18). Xu et al showed that over the past 30 years, the ASIR of kidney cancer has tripled in China (22).…”
Section: Discussionsupporting
confidence: 88%
“…Kidney cancer is one of the 10 cancers with a high incidence rate among the southern Iranian population (17). Studies in Isfahan (Iran) reported the prevalence of kidney and ureteral cancers to be 8.1 and 0.4 per 100 00, respectively (18), and showed that urinary and kidney cancers had a rising trend of incidence, mortality, and prevalence in this region (19). In a study conducted in northern Iran, the standardized incidence of kidney and ureter cancer among women was 0.14 and 0.39, respectively (20).…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study showed that urinary bladder, kidney cancer followed an increasing trend in incidence, mortality and prevalence in Isfahan, Iran (14)(15)(16)(17)(18)(19)(20)(26)(27)(28)(29)(30)(31)(32). The implications of this investigation could be mentioned as the following suggestions: (1) the health care system should provide a model-based strategy to improve access to specialized medical, pharmacological and surgical facilities; (2) consideration is needed toward the reality for scheduling health system improvements, particularly referral systems; (3) preventing significant difficulties by equality of management for patient satisfaction; (4) attention toward financial management by study of epidemiology and pharmacotherapy.…”
Section: Discussionmentioning
confidence: 82%